Automatic defense against zero-day polymorphic worms in communication networks - Mohammed, Mohssen; Pathan, Al-Sakib Khan (CRC Press, USA, 2013)
Internet worms pose a major threat to Internet infrastructure security, and their destruction is truly costly. Computer Worm is a kind of malicious program that self-replicates automatically within a computer network. Worms are in general, a serious threat to computers connected to the Internet and its proper functioning. These malicious programs can spread by exploiting low-level software defects, and can use their victims for illegitimate activities; such as corrupting data, sending unsolicited electronic mail messages, generating traffic for distributed Denial of Service (DoS) attacks, or stealing information. Today, the speed at which the worm propagates poses a serious security threat to the Internet.